Developing the Writing Skills of Social Work Students: Connecting Academic and Professional Expertise - Hughes, Nathan; Wainwright, Sue; Ward, Nicki (Journal of Academic Writing, 2011)
Undergraduate social work education in England requires the completion of the necessary academic credits for an honours degree, alongside the demonstration of the necessary standards and competencies associated with a professional award. This requires a challenging and diverse programme of study. However, the skills necessary for successful academic enquiry complement those required for effective practice. In particular, academic writing skills support effective professional communication and research skills allow for evidence-based practice. This paper describes the development of academic skills within a new undergraduate social work programme at a UK university, designed to meet the needs of a diverse and atypical student cohort. Having recognised the flaws in the early delivery of the programme, a revised curriculum has placed the development of academic research and writing skills at its core.